A Difluoro‐Monobromo End Group Enables High‐Performance Polymer Acceptor and Efficient All‐Polymer Solar Cells Processable with Green Solvent under Ambient Condition. (2nd May 2021) - Yu, Han; Luo, Siwei; Sun, Rui; Angunawela, Indunil; Qi, Zhenyu; Peng, Zhengxing; Zhou, Wentao; Han, Han; Wei, Rong; Pan, Mingao; Cheung, Andy Man Hong; Zhao, Dahui; et al.
Abstract: In this paper, a difluoro‐monobromo end group is designed and synthesized, which is then used to construct a novel polymer acceptor (named PY2F‐T) yielding high‐performance all‐polymer solar cells with 15.22% efficiency. The fluorination strategy can increase the intramolecular charge transfer and interchain packing of the previous PY‐T based acceptor, and significantly improve photon harvesting and charge mobility of the resulting polymer acceptor. In addition, detailed morphology investigations reveal that the PY2F‐T‐based blend shows smaller domain spacing and higher domain purity, which significantly suppress charge recombination as supported by time‐resolved techniques. These polymer properties enable simultaneously enhanced J SC and FF of the PY2F‐T‐based devices, eventually delivering device efficiencies of over 15%, significantly outperforming that of the devices based on the non‐fluorinated PY‐T polymer (13%). More importantly, the PY2F‐T‐based active layers can be processed under ambient conditions and still achieve a 14.37% efficiency. They can also be processed using non‐halogenated solvent o ‐xylene (no additive) and yield a decent performance of 13.05%. This work demonstrates the success of the fluorination strategy in the design of high‐performance polymer acceptors, which provide guidelines for developing new all‐PSCs with better efficiencies and stabilities for commercial applications. Abstract : A novel polymer acceptor PY2F‐T with difluoro‐monobromo end groups on monomer sub‐units is synthesized, exhibiting extended absorption and stronger crystallinity compared to its non‐fluorinated counterpart (PY‐T). When employed in all‐polymer solar cells, the PY2F‐T based device yields an outstanding efficiency of 15.22% and retains a decent performance of 13.05% when processed under ambient conditions with an eco‐friendly solvent ( o ‐xylene, no additive).